Interaction-induced zero-energy pinning and quantum dot formation in Majorana nanowires - Escribano, Samuel D.; Yeyati, Alfredo Levy; Prada, Elsa (Beilstein Journal of Nanotechnology, 2018)
Majorana modes emerge in non-trivial topological phases at the edges of specific materials such as proximitized semiconducting nanowires under an external magnetic field. Ideally, they are non-local states that are charge-neutral superpositions of electrons and holes. However, in nanowires of realistic length their wave functions overlap and acquire a finite charge that makes them susceptible to interactions, specifically with the image charges that arise in the electrostatic environment. Considering a realistic three-dimensional model of the dielectric surroundings, here we show that, under certain circumstances, these interactions lead to a suppression of the Majorana oscillations predicted by simpler theoretical models, and to the formation of low-energy quantum-dot states that interact with the Majorana modes. Both features are observed in recent experiments on the detection of Majoranas and could thus help to properly characterize them.
Keywords: hybrid superconductor–semiconductor nanowires; interactions; Majorana bound states; quantum dots